Harmoni Sosial dalam Perspektif Islam: Tinjauan Terhadap Masyarakat Kontemporer - Ula, Ahmad Nilnal Munachifdlil; Hidayati, Hanik (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This study aims to explore the dynamics of social harmony in the perspective of Islam in contemporary society, considering the influence of global contexts and technological developments. A deep understanding of the religious values of Islam, active involvement in religious activities, and contributions to social activities are the focus of the study. The research method uses a qualitative approach by collecting data through religious literature studies, analyzing government regulations related to social harmony, and direct observation of the social dynamics of contemporary society. The data is then analyzed qualitatively to identify patterns in maintaining social harmony. The results show that understanding religious teachings is the main foundation for maintaining harmony, while active involvement in religious activities and contributions to social activities play a crucial role in forming harmonious social relationships. Challenges related to differences in religious understanding and the impact of global contexts and technological developments highlight the complexity of maintaining social harmony. As a recommendation, this study emphasizes the need for inclusive religious education, promotion of active involvement in religious activities, and strengthening social activities as key steps. Strategies to adapt to global and technological changes are also identified as important steps to overcome these challenges. The conclusion of this study is expected to provide guidance for stakeholders in dealing with the complex dynamics of maintaining social harmony in the perspective of Islam in contemporary society that is constantly changing.